Contribution of pulmonary function tests (PFTs) to the diagnosis and follow up of connective tissue diseases - Ciancio, Nicola; Pavone, Mauro; Torrisi, Sebastiano Emanuele; Vancheri, Ada; Sambataro, Domenico; Palmucci, Stefano; Vancheri, Carlo; Di Marco, Fabiano; Sambataro, Gianluca (Multidisciplinary Respiratory Medicine, 2019)
Introduction: Connective Tissue Diseases (CTDs) are systemic autoimmune conditions characterized by frequent lung involvement. This usually takes the form of Interstitial Lung Disease (ILD), but Obstructive Lung Disease (OLD) and Pulmonary Artery Hypertension (PAH) can also occur. Lung involvement is often severe, representing the first cause of death in CTD. The aim of this study is to highlight the role of Pulmonary Function Tests (PFTs) in the diagnosis and follow up of CTD patients. Main body: Rheumatoid Arthritis (RA) showed mainly an ILD with a Usual Interstitial Pneumonia (UIP) pattern in High-Resolution Chest Tomography (HRCT). PFTs are able to highlight a RA-ILD before its clinical onset and to drive follow up of patients with Forced Vital Capacity (FVC) and Carbon Monoxide Diffusing Capacity (DLCO). In the course of Scleroderma Spectrum Disorders (SSDs) and Idiopathic Inflammatory Myopathies (IIMs), DLCO appears to be more sensitive than FVC in highlighting an ILD, but it can be compromised by the presence of PAH. A restrictive respiratory pattern can be present in IIMs and Systemic Lupus Erythematosus due to the inflammatory involvement of respiratory muscles, the presence of fatigue or diaphragm distress. Conclusions: The lung should be carefully studied during CTDs. PFTs can represent an important prognostic tool for diagnosis and follow up of RA-ILD, but, on their own, lack sufficient specificity or sensitivity to describe lung involvement in SSDs and IIMs. Several composite indexes potentially able to describe the evolution of lung damage and response to treatment in SSDs are under investigation. Considering the potential severity of these conditions, an HRCT jointly with PFTs should be performed in all new diagnoses of SSDs and IIMs. Moreover, follow up PFTs should be interpreted in the light of the risk factor for respiratory disease related to each disease.